BRINGING INNOVATION INTO ENGLISH CLASSROOMS: EXPLORING THE DIFFUSION OF INNOVATION IN ENGLISH LANGUAGE TEACHING - Sri Agriyanti Mestari; Novianty Djafri (Adisam Publisher, 2025)
This study explores the diffusion of innovation in the context of English Language Teaching (ELT). Using Rogers' diffusion of innovation theory as a theoretical framework, the research examines the factors that facilitate or hinder the implementation of innovative practices in English language teaching. Through an extensive literature review, English language teachers in different educational settings are highlighted to understand their perceptions, attitudes and experiences of integrating innovative teaching methods, technologies and materials. The findings show that the rate of adoption of innovations in ELT is influenced by a number of factors, including the perceived characteristics of the innovation, communication channels, time and the social system. Innovative teachers who act as early adopters play a crucial role in the diffusion process by modelling good practice and providing peer support. However, organisational culture, resource constraints and teachers' beliefs also emerge as significant barriers to the widespread diffusion of innovations. The study provides insights into strategies for promoting the successful implementation of innovations in English language teaching. It highlights the importance of creating a supportive environment that encourages risk-taking, provides continuous professional development, and fosters a culture of collaboration and shared learning among English language teachers. The findings have implications for educational policy makers, teacher educators and school administrators in their efforts to improve the quality of English language teaching through innovative approaches.